Blockchain-based skill and employment verification: challenges and strategies for executive hiring in Dubai’s fintech industry - Erceg, Aleksandar; Gollapalli, Huldah; Damoska Sekuloska, Jovanka (Serbian Journal of Management, 2026)
Dubai's traditional executive recruitment process faces challenges, including the use of fake credentials, screening delays, and high recruitment costs. With its decentralized and immutable nature, blockchain offers a potential solution to these problems by ensuring secure, accurate and efficient verification. The paper examines how HR professionals and IT specialists from various Dubai FinTech companies perceive the effectiveness of blockchain in verifying credentials, reducing fraudulent claims, and enhancing recruitment efficiency. Additionally, the paper examines organizations' readiness to adopt blockchain technology and its potential impact on operational costs and efficiency. The research findings show that blockchain significantly improves verification accuracy by reducing human error and preventing fraud. Blockchain has been identified as an effective tool to curb fraudulent claims in executive hiring, positively impacting both time and cost efficiency. However, resistance to new methods and concerns about implementation costs were identified as potential barriers to widespread adoption. To overcome resistance to change and reduce implementation costs, adequate training is essential for successful adoption. The study proposes further research into the long-term adoption of blockchain and its impact on different industries.
Keywords: blockchain; executive recruitment; fraud reduction; skill verification; efficiency; adoption barriers